Prevalence, characteristics and factors associated with alcohol consumption among Peruvian university students during the early stage of the COVID-19 pandemic - Cabanillas Rojas, William (2024)
Objective: To identify the prevalence, characteristics and factors associated with alcohol consumptionamong university students in the Lima Metropolitan Area during the early stage of the COVID-19 pandemic in Peru, from March 16 to June 30, 2020. Materials and methods: A cross-sectional and analytical study was conducted using an online survey administered to 257 students. Descriptive analyses and logistic regressions were performed to determine odds ratios (OR) and their 95 % confidence intervals (95 % CI). The study evaluated the association between alcohol consumption and various sociodemographic, economic and health variables, as well as general and academic stress, fear of COVID-19, third-party provision of alcohol and perceived ease of access to alcohol. Results: A total of 43.6 % of respondents reported consuming alcohol between March and June 2020. Among these, 32.1 % engaged in excessive alcohol consumption and 22.3% experienced episodes of drunkenness. In addition to assessing alcohol consumption in the 12 months preceding the early stage of lockdown, minimal differences were observed in alcohol consumption rates between men and women. During the lockdown, 43.8 % of students reduced their alcohol consumption, while 46.4 % maintained their pre-lockdown consumption levels. Significant associationswere found between alcohol consumption and high levels of general stress (aOR = 2.33; 95 % CI: 1.13-4.75), third-party provision of alcohol (aOR = 13.63; 95 % CI: 6.55-28.3) and perceived ease of access to alcohol (aOR = 4.49; 95 % CI: 1.96-10.3). Conclusions: During the early stage of the COVID-19 pandemic, alcohol consumption among university students was significantly associated with high levelsof general stress, third-party provision of alcohol and perceived ease of access to alcohol. Despite lockdown restrictions, nearly half of the students maintained their pre-pandemic alcohol consumption levels. These findings highlight the need for targeted prevention and intervention strategies addressing alcohol consumption within the university setting.